2013
DOI: 10.1038/jid.2013.187
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of p300 HAT Blocks Cell Cycle Progression, Induces Cellular Senescence, and Inhibits the DNA Damage Response in Melanoma Cells

Abstract: Epigenetic events, including covalent post-translational modifications of histones, have been demonstrated to play critical roles in tumor development and progression. The transcriptional coactivator p300/CBP possesses both histone acetyltransferase (HAT) activity as well as scaffolding properties that directly influence the transcriptional activation of targeted genes. We have used a potent and specific inhibitor of p300/CBP HAT activity, C646, in order to evaluate the functional contributions of p300/CBP HAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 40 publications
8
74
0
Order By: Relevance
“…Compared to acetylation levels at time zero (G 1 -arrested cells), we observed an initial peak of ADA3 acetylation at 4 h followed by a second peak that persisted throughout S and G 2 /M phases. Notably, these dynamic changes in ADA3 acetylation are consistent with previous reports of increases in GCN5 protein levels as cells enter the S phase (33) and a requirement of the HAT activity of p300 for G 1 -S transition (34)(35)(36)(37)(38). Taken together, our results demonstrate that ADA3 acetylation is cell cycle dependent and raised the possibility that acetylation of ADA3 regulates its function in cell cycle progression.…”
Section: Ada3 Acetylation Levels Change During Cell Cycle Progressionsupporting
confidence: 81%
See 1 more Smart Citation
“…Compared to acetylation levels at time zero (G 1 -arrested cells), we observed an initial peak of ADA3 acetylation at 4 h followed by a second peak that persisted throughout S and G 2 /M phases. Notably, these dynamic changes in ADA3 acetylation are consistent with previous reports of increases in GCN5 protein levels as cells enter the S phase (33) and a requirement of the HAT activity of p300 for G 1 -S transition (34)(35)(36)(37)(38). Taken together, our results demonstrate that ADA3 acetylation is cell cycle dependent and raised the possibility that acetylation of ADA3 regulates its function in cell cycle progression.…”
Section: Ada3 Acetylation Levels Change During Cell Cycle Progressionsupporting
confidence: 81%
“…Such dynamic regulation during cell cycle progression further supports the functional role of ADA3 acetylation, suggesting regulation at the levels/activities of HATs/HDACs targeting the acetylation/deacetylation of ADA3. The transient earlier peak and more sustained delayed ADA3 acetylation during cell cycle progression may reflect the relative activities of GCN5 and p300, a possibility consistent with the reported increase in GCN5 levels from G 1 to early S phase (33) and the requirement for p300 HAT activity for progression through S phase (34)(35)(36)(37)(38). If established in future studies, such a scheme will support distinct roles for GCN5/ PCAF-versus p300-mediated acetylation of ADA3.…”
Section: Discussionsupporting
confidence: 57%
“…S4A). Earlier studies have claimed that doxorubicin was effective at killing colorectal cancer cells (31) and that C646 was able to inhibit their growth (32). Although our cell viability assays hinted a slight p53-dependent protection of HCT116 cells by C646 against doxorubicin ( Fig.…”
Section: Addressing the Safety Concerns Of C646mentioning
confidence: 47%
“…Previous studies have reported that a combination of HDACIs, such as TSA combined with curcumin, produced significant antiproliferative and apoptotic effects compared with either agent alone. 40 The combination of quercetin and TSA significantly increased the cytotoxic effect in A549 cells, 41 whereas that of TSA and PdNPs produced a significant inhibitory effect on cell survival and HDAC activity in HeLa cells. In order to determine the correlation between cell viability and HDAC activity, we first evaluated the combinatorial effect of TUB-A and PdNPs on cell viability and HDAC activity in MDA-MB-231 human breast cancer cells.…”
Section: Results and Discussion Synthesis And Characterization Of Pdnpsmentioning
confidence: 99%